Care work of left-behind fathers in a transnational family - Pupos, Vera Eileen V.; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
This is a qualitative exploratory research on the care work of left behind fathers in a transnational family. This study interviewed 14 left behind fathers, seven employed and seven unemployed, who are living under one roof and are the primary care takers of the left behind children ages 0 to 12 years old. They have been a transnational family for at least three years, and so it is presumed that they have already surpassed the tremendous disequilibrium brought about by the departure of the mother, and have been able to gain homeostasis in terms of living day after day without the physical presence of the mother. The study identified the challenges, motivations, coping strategies, factors influencing care work and the extent of involvement of the left behind fathers in a transnational family. This study found that their greatest challenge is not in doing household chores but in nurturing the children. They said that doing household chores can be learned and easy to do however, nurturing the children goes beyond performing, and requires connecting with and understanding their feelings and needs. The study also observed that the children are the left behind fathers greatest motivator, and one of their coping strategies is reciprocating the sacrifice of the mother which made them perform the responsibilities lodged on them. It is the affection of the children towards them, the thought that the children need them and that they have to take care of them make them wake up each day and continue their role as father and at the same time try as much as possible to be like the childrens much needed mother.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Migrant laborer's spouses -- Philippines -- Metro Manila; Househusbands -- Philippines -- Metro Manila; Fathers -- Philippines -- Metro Manila